Factors Affecting Lactation Length and Peak Milk Yield in Gir Cattle - Dangar, Nikhil S; Vataliya, Pravin H (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
The production records of 228 Gir cows with 680 lactations sired by 52 bulls, maintained at Cattle Breeding Farm, Junagadh, were studiedfor 24 years (1987-2010). The data were analyzed to study the effect of period of calving, season of calving and parity as fixed effect onthe production traits, viz., lactation length and peak milk yield. The least squares means of lactation length and peak milk yield in Gircows were found to be 328.27 ± 12.99 days and 12.31 ± 0.51 kg, respectively. The variance analysis revealed that the period of calving andparity had a highly significant (p
Keywords: : Gir cattle; Lactation length, Peak milk yield; Factors influencing